TACIT COLLUSION UNDER COMPETITION LAW: PRICING ALGORITHMS - Stella Solernou SANZ (Challenges of the Knowledge Society)
A great level of transparency, resulting from data sharing (exchange of information), combined with use of algorithms may lead to reciprocal price or production control by competitors. Algorithms eliminate elements of spontaneity in market and may result in supracompetitive prices. But the collusive effect can also occur even if economic operators do not have this intention. Not always there is an express or implied agreement that fits within the concept of "restriction of competition", as traditionally delimited by European case law in the sense that companies agree to eliminate their independence or freedom to defining their business strategy. In these cases, there may not even have been any concerted practice; each operator, using specific algorithms, which observe and analyse competitors' historical price data, sets its own prices and determines those of rivals. According to the European Commission, in the context of e-commerce, European retailers are already starting to set their prices on the basis of those set by their competitors, using automatic computer developments. In this way it unilaterally provokes collusion (higher prices). This makes it difficult to apply article 101 TFEU, since it requires some kind of concerted practice involving the idea of agreement. It is necessary to analyse whether it is possible to reinterpret the rule in such a way as to include the phenomenon of tacit collusion.